2005
DOI: 10.1146/annurev.publhealth.26.021304.144402
|View full text |Cite
|
Sign up to set email alerts
|

ADVANCES IN CANCER EPIDEMIOLOGY: Understanding Causal Mechanisms and the Evidence for Implementing Interventions

Abstract: ■ Abstract In a worldwide population of 6 billion, in the year 2000, approximately 10 million cancers were diagnosed, and there were an estimated 6.2 million cancer deaths. Whereas the universality of cancer incidence and mortality is established, the burden of cancer by type or organ site is distributed unequally between developing and industrialized nations. Populations in developing countries are disproportionately affected by cancers in which infectious agents are causal. Our review of advances in cancer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 94 publications
1
32
0
2
Order By: Relevance
“…In chronic inflammation, NF-κB has a specific role in coupling inflammation to cancer. In total, >15% of all malignancies are initiated by chronic inflammatory disease; for example, skin inflammation initiates squamous cell carcinoma, viral hepatitis initiates liver cancer and inflammatory bowel disease (IBD) initiates CRC (31,(37)(38)(39)(40)(41). Previous studies have indicated that constitutive NF-κB activation in IBDs may be the cause of the increased risk of developing CRC (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic inflammation, NF-κB has a specific role in coupling inflammation to cancer. In total, >15% of all malignancies are initiated by chronic inflammatory disease; for example, skin inflammation initiates squamous cell carcinoma, viral hepatitis initiates liver cancer and inflammatory bowel disease (IBD) initiates CRC (31,(37)(38)(39)(40)(41). Previous studies have indicated that constitutive NF-κB activation in IBDs may be the cause of the increased risk of developing CRC (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…31 However, environmental factors have also been shown to play an important role in the regulation of cancer initiation, development, and aggressiveness. 32 One such factor that is now well-recognized to play an important role in this process is the diet. 33 Dietary cholesterol has an important role in the regulation of plasma cholesterol metabolism.…”
Section: Diet Cholesterol and Cancermentioning
confidence: 99%
“…It has been estimated that more than 15% of all malignancies are initiated by chronic inflammatory disease (40)(41)(42)(43)(44)(45). In Table 1, an outline is given of inflammation that has been associated with cancer development: skin inflammation with squamous cell carcinoma, viral hepatitis with liver cancer and inflammatory bowel disease with colorectal cancer.…”
Section: Nf-b Links Inflammation To Cancermentioning
confidence: 99%